Mitigation of Climate Change through Conservation Agriculture in Europe - Basch, G. (2018)
Agriculture and climate change are closely related. In this communication, the European Conservation Agriculture Federation (ECAF) presents how the European agricultural sector can respond to climate change through Conservation Agriculture (CA). It is based on the outcomes and the realization of several European (LIFE) public-funded projects based on the assessment of CA performance in Europe, and on a literature review on the topic. In terms of contribution, approximately 10% of greenhouse gases (GHGs) globally emitted come from the European Union (EU). Within the GHGs emitted in Europe, around 10% derive from agriculture. In order to reduce these emissions the 21st meeting of the Conference of the Parties (COP21) and the 11th meeting of the Conference of the Parties serving as the meeting of the Parties to the Kyoto Protocol (CMP) was held at the end of 2015 in Paris. It concluded with the adoption of a historic agreement to combat climate change and promote measures and investments for a low-carbon, resilient and sustainable future, the so-called Paris Agreement. Scientiﬁc studies, carried out in diﬀerent European biogeographic regions and countries, agree that the less soil is tilled, the more carbon is sequestered and stored in it. These studies show that, during several years of Conservation Agriculture, it is possible to sequester large amounts of CO2 per hectare and year in soils, when compared to systems based on soil tillage. In relation to conventional tillage systems the implementation of CA in EU-28 countries in both annual and perennial crops could result in an annual sequestration of almost 190 millions of tons CO2 as soil organic carbon. The amount of CO2 sequestered into the soil through the application of the CA would contribute signiﬁcantly to reach the targets committed in Paris Agreement by 2030. Considering accepted European emission reduction targets, carbon sequestration that could take place on farmland under Conservation Agriculture would amount to 22% of reductions committed in all diﬀ use emission sectors by 2030, which corresponds to 10% of total annual diﬀ use emissions. This would allow for some ﬂexibility in the reduction of emissions in other sectors such as housing or transport.